Transpositions : Aesthetico-Epistemic Operators in Artistic Research - Arlander, Annette; Braidotti, Rosi; de Assis, Paulo (Leuven University Press, 2018)
Research leads to new insights rupturing the existent fabric of knowledge. Situated in the still evolving field of artistic research, this book investigates a fundamental quality of this process. Building on the lessons of deconstruction, artistic research invents new modes of epistemic relationships that include aesthetic dimensions. Under the heading transposition, seventeen artists, musicians, and theorists explain how one thing may turn into another in a spatio-temporal play of identity and difference that has the power to expand into the unknown. By connecting materially concrete positions in a way familiar to artists, this book shows how moves can be made between established positions and completely new ground. In doing so, research changes from a process that expands knowledge to one that creatively reinvents it.
English
Keywords: Techniques of music / music tutorials; Theory of music & musicology; Music; Instruction & Study; Music; Philosophy & Social Aspects